HISTORICAL AND MANAGEMENT ASPECTS OF VETERINARY MEDICINE DEVELOPMENT IN UKRAINIAN LANDS IN 11 TH – 17 TH CENTURIES - Didok Yu.V. (Pressing Problems of Public Administration, 2018)
The article is devoted to studying of historical and management aspects of the veterinary medicine development of Ukraine in the period of the 11TH – 17TH centuries. The features of public administration and the state of veterinary medicine development in the territory of Ukrainian lands in the times of Kievan Rus, the Tatar-Mongol invasion, the Lithuanian and Polish domination and the Cossack era have been characterized. The expedience of considering the said historical periods as a stage of forming prerequisites for the public administration in the  eld of veterinary medicine in Ukraine has been substantiated. Historical achievements of this historical period in terms of their value for the development of veterinary medicine as a branch have been determined.